2022
DOI: 10.1002/ptr.7460
|View full text |Cite
|
Sign up to set email alerts
|

Natural product‐based nanomedicine applied to fungal infection treatment: A review of the last 4 years

Abstract: Fungal infections are one of the main public health problems, especially in immunocompromised patients, nosocomial environments, patients with chronic diseases, and transplant recipients. These diseases are increasingly frequent and lethal because the microorganism has a high capacity to acquire resistance to available therapy. The main resistance factors are the emergence of new strains and the uncontrolled use of antifungals. It is, therefore, important to develop new methods that contribute to combating fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 295 publications
(377 reference statements)
0
4
0
Order By: Relevance
“…203,[205][206][207][208][209][210] Some of the formulations such as Abelcet@, Ambisome@, Fungizone@, and Amphotec@ are commercially available liposome-based nanocarriers for amphotericin B delivery, approved in 1990s. 211,212 Such lipid NPs have been further modified with polymers such as chitosan for a mucoadhesive buccal drug delivery system for candidiasis. 213,214 Another study focused on using Nystatin, a poorly soluble polyene antifungal drug for treating oral candidiasis.…”
Section: Oral Fungal Infectionmentioning
confidence: 99%
“…203,[205][206][207][208][209][210] Some of the formulations such as Abelcet@, Ambisome@, Fungizone@, and Amphotec@ are commercially available liposome-based nanocarriers for amphotericin B delivery, approved in 1990s. 211,212 Such lipid NPs have been further modified with polymers such as chitosan for a mucoadhesive buccal drug delivery system for candidiasis. 213,214 Another study focused on using Nystatin, a poorly soluble polyene antifungal drug for treating oral candidiasis.…”
Section: Oral Fungal Infectionmentioning
confidence: 99%
“…They reported a mm inhibition zone at 6.8 µg/mL concentration. A review on the use of natural-product-based nanomedicine has recently been published, which helps to rationalize such development [126]. In a similar manner, Gruzman, Cohen et al described the 8-step synthesis of novel sulfamoylbenzoates and their subsequent inhibition of M. furfur growth.…”
Section: Bio-inspired Compoundsmentioning
confidence: 99%
“…They reported a 20.5 mm inhibition zone at 6.8 µg/mL concentration. A review on the use of natural-product-based nanomedicine has recently been published, which helps to rationalize such development [126].…”
Section: Bio-inspired Compoundsmentioning
confidence: 99%
“…The development of new hybrid compounds specific to Tau protein is therefore a more attractive approach to directly affect microtubules. In this regard, flavonoid derivatives, including flavonol and flavone, constitute a substantial class of naturally occurring compounds with diverse pharmacological properties such as antitumor, antibacterial, immune-stimulator, antifungal, and antidiabetic activities in addition to anti-Tau fibrils properties [28][29][30][31][32][33]. For example, Sonawane et al recently showed in vitro that Baicalein inhibited formation of Tau fibrils by enhancing the formation of SDS-stable oligomers [34].…”
Section: Introductionmentioning
confidence: 99%